Sodium ferric sulfate positive electrode material and preparation method thereof, sodium ion battery and electric equipment

By mixing ball mill and sintering in an inert atmosphere, a sodium ferrosulfate positive electrode material with high conductivity and good air stability was prepared, solving the problems of poor conductivity and poor air stability of the existing materials.

CN119612599APending Publication Date: 2025-03-14GUIZHOU WEIFANG ENERGY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738915.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing sodium ferrosulfate positive electrode materials have poor conductivity and poor air stability of the material.

Method used

The sodium ferrous sulfate positive electrode material was prepared by ball milling and mixing the ferrous sulfate, sodium sulfate, boron nitride and carbon materials, and then sintering in an inert atmosphere.

Benefits of technology

The conductivity and air stability of the sodium ferric sulfate cathode material are improved, and its sodium storage and rate performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612599A_ABST
    Figure CN119612599A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ferric sulfate positive electrode material and a preparation method thereof, a sodium ion battery and electric equipment, and relates to the technical field of new energy. The preparation method of the sodium ferric sulfate positive electrode material comprises the following steps: mixing ferrous sulfate, sodium sulfate, boron nitride and a carbon material through ball milling to obtain a mixture; and sintering the mixture in an inert atmosphere to obtain the sodium ferric sulfate positive electrode material. The preparation method disclosed by the invention is simple in process and convenient for expanded production, and the synthesized sodium ferric sulfate has relatively high conductivity, relatively good sodium storage performance and relatively good rate capability. According to the sodium ion battery and the electric equipment, due to the fact that the sodium ferric sulfate positive electrode material prepared through the method is adopted, the first charge capacity can reach 102.27 mAh / g, the first discharge capacity can reach 100.03 mAh / g, the capacity retention rate can reach 96.24% after 1000 cycles under the 5C multiplying power, and the capacity retention rate can reach 81.41% under the 20C multiplying power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a sodium iron sulfate positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art

[0002] Electrochemical energy storage has the characteristics of high utilization rate and flexible use. Among them, lithium-ion batteries, as the mainstream battery for energy storage, have the advantages of high specific capacity, high voltage, long cycle life, and stable discharge performance, but the scarcity of lithium resources will limit its application in the field of large-scale energy storage. Therefore, the development of a battery system with low cost and good performance is the key. The energy storage of sodium resources is extremely abundant, hundreds of times that of lithium resources, which has made sodium-ion batteries widely concerned. The positive electrode material of sodium-ion batteries has a great influence on the electrochemical performance of the battery. Among them, sodium iron sulfate has the advantages of high voltage, good cycle performance, and low cost, but it also has disadvantages such as poor conductivity and poor air stability of the material. Summary of the invention

[0003] The purpose of the present application is to provide a sodium iron sulfate positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment, aiming to solve the problems of poor conductivity and poor air stability of existing sodium iron sulfate positive electrode materials.

[0004] To achieve the above objectives, the present application provides a method for preparing a sodium iron sulfate positive electrode material, comprising:

[0005] Mixing ferrous sulfate, sodium sulfate, boron nitride and carbon material by ball milling to obtain a mixture;

[0006] The mixed material is sintered in an inert atmosphere to obtain a sodium iron sulfate positive electrode material.

[0007] In some embodiments, the molar ratio of the ferrous sulfate, the sodium sulfate, and the boron nitride is (2-6):(2-4):(0.01-0.3).

[0008] In some embodiments, the carbon material includes at least two of Ketjen black, graphene oxide, graphite powder, carbon nanotubes, citric acid, glucose, and sorbic acid.

[0009] In some embodiments, the mass of the carbon material is 3% to 10% of the total mass of the ferrous sulfate, the sodium sulfate and the boron nitride.

[0010] In some embodiments, the ball milling speed is 300 r / min to 600 r / min, and the time is 3 h to 8 h.

[0011] In some embodiments, at least one of the following conditions is met:

[0012] A. The heating rate of the sintering is 1°C / min to 5°C / min;

[0013] B. The sintering temperature is 300°C to 400°C;

[0014] C. The sintering time is 8h to 24h.

[0015] In some embodiments, the inert gas is nitrogen or argon.

[0016] The present application also provides a sodium iron sulfate positive electrode material, which is prepared by the above-mentioned method for preparing the sodium iron sulfate positive electrode material.

[0017] The present application also provides a sodium ion battery, comprising the above-mentioned sodium iron sulfate positive electrode material.

[0018] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0019] Compared with the prior art, the beneficial effects of this application include:

[0020] The preparation method of the sodium ferric sulfate positive electrode material provided in the present application comprises mixing ferrous sulfate, sodium sulfate, boron nitride, and carbon material by ball milling to obtain a mixture; and sintering the mixture in an inert atmosphere to obtain the sodium ferric sulfate positive electrode material. The preparation method provided in the present application has a simple process and is easy to expand production, and the synthesized sodium ferric sulfate has high electrical conductivity, good sodium storage performance, and good rate performance, and the boron nitride has antioxidant properties, which can reduce the reaction between the sodium ferric sulfate positive electrode material and oxygen and other gases in the air, and improve the air stability of the material.

[0021] The sodium ion battery and electrical equipment provided in the present application have a first charge capacity of 102.27 mAh / g and a first discharge capacity of 100.03 mAh / g due to the use of the sodium iron sulfate positive electrode material prepared in the present application. The capacity retention rate after 1000 cycles at a 5C rate can reach 96.24%, and the capacity retention rate at a 20C rate can reach 81.41%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0023] Figure 1 A schematic diagram of a process for preparing the sodium iron sulfate positive electrode material of the present application;

[0024] Figure 2X-ray diffraction (XRD) images of the sodium iron sulfate positive electrode material of Example 1 and the material of Comparative Example 5;

[0025] Figure 3 This is the charge and discharge curve of the sodium iron sulfate positive electrode material of Example 1;

[0026] Figure 4 This is a cycle diagram of the sodium iron sulfate positive electrode material of Example 1;

[0027] Figure 5 This is a rate performance diagram of the sodium iron sulfate positive electrode material of Example 1;

[0028] Figure 6 The impedance diagram of the sodium iron sulfate positive electrode material of Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0029] As used herein:

[0030] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0031] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0032] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0033] In these examples, parts and percentages are by mass unless otherwise indicated.

[0034] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0035] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0037] This application provides a method for preparing a sodium iron sulfate positive electrode material. Figure 1 ,include:

[0038] S100: mixing ferrous sulfate, sodium sulfate, boron nitride and carbon material by ball milling to obtain a mixture;

[0039] S200: sintering the mixture in an inert atmosphere to obtain a sodium iron sulfate positive electrode material.

[0040] The preparation method of the sodium ferric sulfate positive electrode material provided in the present application has a simple process and is easy to expand production. The synthesized sodium ferric sulfate has high electrical conductivity, good sodium storage performance and good rate performance. Boron nitride has antioxidant properties, which can reduce the reaction between the sodium ferric sulfate positive electrode material and oxygen and other gases in the air, thereby improving the air stability of the material.

[0041] In some embodiments, the molar ratio of ferrous sulfate, sodium sulfate, and boron nitride in step S100 is (2-6):(2-4):(0.01-0.3), the molar ratio of ferrous sulfate can be, for example, 2, 3, 4, 5, 6 or any value between 2 and 6, the molar ratio of sodium sulfate can be, for example, 2, 3, 4 or any value between 2 and 4; the molar ratio of boron nitride can be, for example, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 or any value between 0.01 and 0.3.

[0042] The sodium ferric sulfate positive electrode material obtained by using ferrous sulfate, sodium sulfate and boron nitride within the above-mentioned dosage ratio range has good performance. If the amount of boron nitride exceeds the above-mentioned range, it will be excessively coated on the material, affecting the insertion and extraction of ions; if the amount of boron nitride is lower than the above-mentioned range, the electrochemical performance of the material is poor.

[0043] In some embodiments, the carbon material in step S100 includes at least two of Ketjen black, graphene oxide, graphite powder, carbon nanotubes, citric acid, glucose, and sorbic acid, for example, a combination of two, three, four, five or more thereof.

[0044] In some embodiments, the mass of the carbon material in step S100 is 3% to 10% of the total mass of ferrous sulfate, sodium sulfate and boron nitride, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 3% and 10%.

[0045] In some embodiments, the rotation speed of the ball mill in step S100 is 300r / min to 600r / min, for example, it can be 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min or any value between 300r / min and 600r / min, and the time is 3h to 8h, for example, it can be 3h, 4h, 5h, 6h, 7h, 8h or any value between 3h and 8h.

[0046] In some embodiments, the heating rate of sintering in step S200 is 1°C / min to 5°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min and 5°C / min.

[0047] In some embodiments, the sintering temperature in step S200 is 300° C. to 400° C., for example, 300° C., 310° C., 320° C., 330° C., 340° C., 350° C., 360° C., 370° C., 380° C., 390° C., 400° C., or any value between 300° C. and 400° C. If the sintering temperature is too high, sulfate ions will decompose and the target material cannot be obtained.

[0048] In some embodiments, the sintering time in step S200 is 8 h to 24 h, for example, it can be 8 h, 10 h, 12 h, 14 h, 15 h, 17 h, 19 h, 20 h, 22 h, 24 h or any value between 8 h and 24 h.

[0049] In some embodiments, the inert gas is nitrogen or argon.

[0050] The present application also provides a sodium iron sulfate positive electrode material, which is prepared by the above-mentioned method for preparing the sodium iron sulfate positive electrode material.

[0051] The present application also provides a sodium ion battery, comprising the above-mentioned sodium iron sulfate positive electrode material.

[0052] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0053] The sodium ion battery and electrical equipment provided in the present application have a first charge capacity of 102.27 mAh / g and a first discharge capacity of 100.03 mAh / g due to the use of the sodium iron sulfate positive electrode material prepared in the present application. The capacity retention rate after 1000 cycles at a 5C rate can reach 96.24%, and the capacity retention rate at a 20C rate can reach 81.41%.

[0054] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0055] Example 1

[0056] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0057] Ferrous sulfate, sodium sulfate, and boron nitride were weighed in a molar ratio of 5:3:0.05, and then 2.5% of Ketjen black, 2.5% of graphene oxide, and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate, and boron nitride were added, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace and heated to 350° C. at a rate of 2° C. / min, and kept warm for 12 h. The sodium iron sulfate positive electrode material of Example 1 was obtained by natural cooling. Its XRD results are shown as follows: Figure 2 shown.

[0058] Example 2

[0059] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0060] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.15, and 2.5% of Ketjen black, 2.5% of graphene oxide and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and the mixture was ball-milled at 400r / min for 6h. The ball-milled mixture was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 350°C, kept warm for 12h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Example 2.

[0061] Example 3

[0062] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0063] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.01, and 2.5% of Ketjen black, 2.5% of graphene oxide and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 350°C, kept warm for 12 h, and naturally cooled to obtain the sodium ferric sulfate powder of Example 3.

[0064] Example 4

[0065] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0066] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.3, and 2.5% of Ketjen black, 2.5% of graphene oxide and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 350°C, kept warm for 12 h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Example 4.

[0067] Example 5

[0068] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0069] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 2:2:0.05, and 2.5% of Ketjen black, 2.5% of graphene oxide and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 350°C, kept warm for 12 h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Example 5.

[0070] Example 6

[0071] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0072] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:4:0.05, and 2.5% of Ketjen black, 2.5% of graphene oxide and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and ball milled at 400r / min for 6h. The ball-milled mixture was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 350°C, kept warm for 12h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Example 6.

[0073] Example 7

[0074] This embodiment provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0075] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.05, and 2.5% of Ketjen black and 2.5% of graphene oxide accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace and heated to 350° C. at a rate of 2° C. / min, kept warm for 12 h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Example 7.

[0076] Comparative Example 1

[0077] This comparative example provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0078] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.05, and 5% of the total mass of ferrous sulfate, sodium sulfate and boron nitride was added with Ketjen black, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace and heated to 350°C at a rate of 2°C / min, kept warm for 12 h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Comparative Example 1.

[0079] Comparative Example 2

[0080] This comparative example provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0081] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.05 without adding carbon material, and ball-milled at 400 r / min for 6 h. The ball-milled solid was placed in an argon atmosphere furnace and heated to 350°C at a rate of 2°C / min, kept warm for 12 h, and naturally cooled to obtain the sodium ferric sulfate positive electrode material of Comparative Example 2.

[0082] Comparative Example 3

[0083] This comparative example provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0084] Ferrous sulfate and sodium sulfate were weighed in a molar ratio of 5:3, and 2.5% of Ketjen black, 2.5% of graphene oxide, and 2.666% of citric acid accounting for the total mass of ferrous sulfate and sodium sulfate were added, and ball milling was carried out at 400r / min for 6h. The ball-milled solid was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 350°C, kept warm for 12h, and naturally cooled to obtain the sodium ferric sulfate positive electrode material of Comparative Example 3.

[0085] Comparative Example 4

[0086] This comparative example provides a sodium iron sulfate positive electrode material, and the preparation method thereof comprises the following steps:

[0087] Ferrous sulfate, sodium sulfate and boron nitride were weighed in a molar ratio of 5:3:0.4, and 2.5% of Ketjen black, 2.5% of graphene oxide and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate and boron nitride were added, and ball milling was carried out at 400r / min for 6h. The ball-milled solid was placed in an argon atmosphere furnace and heated to 350°C at a rate of 2°C / min, kept warm for 12h, and naturally cooled to obtain the sodium iron sulfate positive electrode material of Comparative Example 4.

[0088] Comparative Example 5

[0089] This comparative example provides a material, and its preparation method comprises the following steps:

[0090] Ferrous sulfate, sodium sulfate, and boron nitride were weighed in a molar ratio of 5:3:0.05, and then 2.5% of Ketjen black, 2.5% of graphene oxide, and 2.666% of citric acid accounting for the total mass of ferrous sulfate, sodium sulfate, and boron nitride were added, and the mixture was ball-milled at 400 r / min for 6 h. The ball-milled mixture was placed in an argon atmosphere furnace at a heating rate of 2°C / min to 450°C, kept warm for 12 h, and naturally cooled to obtain the material of Comparative Example 5. Its XRD results are shown as follows: Figure 2 As shown, it is proved that the material sintered at 450℃ is not sodium iron sulfate. Testing has found that the sintered material has no capacity.

[0091] The sodium iron sulfate positive electrode materials prepared in Examples 1-7 and Comparative Examples 1-4 were mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added. After being stirred on a magnetic stirrer for about 6 hours, a positive electrode slurry was obtained. The slurry was coated on aluminum foil with a coating machine, placed in a vacuum drying oven at 120°C, and dried for about 12 hours. After being taken out, it was cut into small discs with a diameter of 16 mm with a slicer, and then pressed to 20 Mp with a tablet press, and the pressure was maintained for 30 seconds. Finally, the positive electrode sheets of Examples 1-7 and Comparative Examples 1-4 were obtained. The button batteries were assembled according to the negative electrode shell, spring sheet, gasket, sodium sheet negative electrode, diaphragm, electrolyte, positive electrode sheet and positive electrode shell, and the electrochemical performance was tested in the voltage range of 2V-4.5V. The electrochemical performance data obtained are shown in Table 1. The charge and discharge curves of the sodium iron sulfate positive electrode material in Example 1 are shown in Table 1. Figure 3 As shown, 1st represents the first cycle, 2nd represents the second cycle, and 3rd represents the third cycle. The cycle diagram of the sodium iron sulfate positive electrode material of Example 1 is as shown in Figure 4 As shown in the figure, the rate performance diagram is as follows Figure 5 shown.

[0092] Table 1 Electrochemical properties of sodium iron sulfate positive electrode materials of various embodiments and comparative examples

[0093]

[0094] According to Table 1, compared with the addition of two or more carbon materials in Examples 1 to 7, Comparative Example 1 only adds one carbon material, and Comparative Example 2 does not add a carbon material. The electrochemical performance of the sodium iron sulfate positive electrode materials in Comparative Example 1 and Comparative Example 2 is significantly reduced compared with the examples. Comparative Example 3 does not add boron nitride, and the capacity and cycle performance of the obtained sodium iron sulfate positive electrode material are also inferior to those of the examples; however, the amount of boron nitride added in Comparative Example 4 is too high, which is not conducive to improving the capacity and cycle performance of the sodium iron sulfate positive electrode material.

[0095] Figure 6 The impedance diagram of the sodium ferric sulfate positive electrode material of Example 1 and Comparative Example 3. The larger the diameter of the semicircle in the figure, the greater the impedance, indicating that the impedance of the sodium ferric sulfate positive electrode material of Comparative Example 3 is significantly higher than the impedance of the sodium ferric sulfate positive electrode material of Example 1, and the impedance and conductivity are inversely proportional, indicating that the conductivity of the sodium ferric sulfate positive electrode material of Example 1 is higher than the conductivity of the sodium ferric sulfate positive electrode material of Comparative Example 3.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0097] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: include: Mixing ferrous sulfate, sodium sulfate, boron nitride and carbon material by ball milling to obtain a mixture; The mixed material is sintered in an inert atmosphere to obtain a sodium iron sulfate positive electrode material.

2. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The molar ratio of the ferrous sulfate, the sodium sulfate and the boron nitride is (2-6):(2-4):(0.01-0.3).

3. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The carbon material includes at least two of Ketjen black, graphene oxide, graphite powder, carbon nanotubes, citric acid, glucose, and sorbic acid.

4. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The mass of the carbon material is 3% to 10% of the total mass of the ferrous sulfate, the sodium sulfate and the boron nitride.

5. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The ball mill has a rotation speed of 300 r / min to 600 r / min and a milling time of 3 h to 8 h.

6. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. The heating rate of the sintering is 1°C / min to 5°C / min; B. The sintering temperature is 300°C to 400°C; C. The sintering time is 8h to 24h.

7. The method for preparing the sodium iron sulfate positive electrode material according to any one of claims 1 to 6, characterized in that: The inert gas is nitrogen or argon.

8. A sodium iron sulfate positive electrode material, characterized in that: The sodium iron sulfate positive electrode material is prepared by the preparation method of the sodium iron sulfate positive electrode material according to any one of claims 1 to 7.

9. A sodium ion battery, characterized in that: Including the sodium iron sulfate positive electrode material as described in claim 8.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.